Martial arts, combat sports, and mental health in adults: A systematic review - Ciaccioni, S.; Castro, O.; Bahrami, F.; Tomporowski, F. D.; Capranica, L.; Biddle, S. J. H.; Vergeer, I.; Pesce, C. (Psychology of Sport and Exercise, 2024)
Martial arts (MA) and combat sports (CS) are physical activities that may be associated with health-related outcomes. The aim of this systematic review was to synthesize and evaluate the available evidence on the relationship between MA and CS training and mental health of adult practitioners (=18 years). CochraneLibrary, EBSCOhost, Web-of-Science, and Scopus databases were searched up to September 2022 for measures of self-related constructs, ill-being and well-being, cognition and brain structure/function, in adult MA/CS practitioners. Seventy cross-sectional and two longitudinal studies were retained and submitted to risk of bias assessments through an adapted version of the Cochrane Collaboration`s Tool. Associations between MA/CS practice and self-related constructs were inconclusive for both consistency and strength of evidence. Limited evidence of significant associations emerged for sub-domains of ill-being (i.e., externalizing and internalizing emotion regulation), and well-being. In regard to cognitive and brain structural/functional variables, evidence of positive association with MA/CS practice was consistent with respect to perceptual and inhibition abilities but limited with respect to attention and memory. Evidence on negative associations of boxing with changes of brain structure integrity due to concussions was also inconclusive. Functional imaging techniques could shed light onto brain activation mechanisms underlying complex cognitive performance. In relation to moderators, mixed results were found for activity exposure, expertise, level of competitive engagement (which often covary with the length of training) and sex and type of MA/CS. The MA/CS` multifaceted nature may produce different, sometimes conflicting outcomes on mental health. Studies on MA/CS represent a flourishing research area needing extensive improvement in theoretical and practical approaches.